The neuroprotective effect of ethanolic extract Ocimum sanctum Linn. in the regulation of neuronal density in hippocampus areas as a central autobiography memory on the rat model of Alzheimer's disease - Mataram, M.B.A.; Hening, P.; Harjanti, F.N.; Karnati, S.; Wasityastuti, W.; Nugrahaningsih, D.A.A.; Kusindarta, D.L.; Wihadmadyatami, H. (2021)
The aim of this study was to identify the effects of Ocimum sanctum Linn. ethanolic extract (OSE) on the neurons of the CA1, CA3, and DG hippocampal areas with the use of in vivo and in vitro models of Alzheimer's diseases (AD). Twenty-one two-month-old male rats were divided into three groups: untreated (Group A, n = 3), AD rats model pretreated with OSE followed by induction for Trimethyltin (TMT) on day 7 (group B, n = 9), and AD rats model treated with OSE both as pre-TMT introduction for 7 days and post-TMT induction for 21 days (group C, n = 9). AD rats were sacrificed on days 7, 14, and 21, and brain samples were collected and analyzed for neuronal density and neuropeptide Y (NPY) immunoreactivity. To corroborate the in vivo observations, HEK-293 cells were treated with TMT and used as an in vitro model of AD. The results were then analyzed using FITC Annexin V and flow cytometry. Nuclear fragmentation was observed in cells stained with Hoechst 33342 by confocal microscopy. The results showed a significant increase in the number of neurons and NPY expression in the AD rats that were pre- and post-treated with OSE (p < 0.05). Indeed, OSE was able to retain and promote neuronal density in the rat model of AD. Further studies of an in vitro model of neurodegeneration with Ocimum sanctum Linn. ethanolic extract inhibited apoptosis in TMT-induced HEK-293 cells. Moreover, OSE prevented nuclear fragmentation, which was confirmed by staining the nuclei of HEK-293 cells. Taken together, there findings suggest that OSE has the potential as a neuroprotective agent (retaining the autobiographical memory),and the neuroproliferation of neurons in the CA1, CA3, and DG hippocampal areas in the ratsÂ¡ model of neurodegeneration was mediated by activation of NPY expression. Â© 2020 Elsevier B.V.